2015
DOI: 10.3310/hsdr03260
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the evidence on employee engagement and its potential benefits to NHS staff: a narrative synthesis of the literature

Abstract: BackgroundRecent studies have suggested engagement is linked with beneficial outcomes for individuals and organisations. Despite growing demand for resources and advice on engagement within the NHS, there has been no systematic evaluation of how engagement strategies can be developed and operationalised within the NHS.Objectives and research questionsTo evaluate evidence and theories of employee engagement within the NHS and the general workforce to inform policy and practice. Four research questions focused o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
50
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(68 citation statements)
references
References 262 publications
(475 reference statements)
4
50
0
Order By: Relevance
“…The current literature lacks the studies that investigate the relationship of low financial income and work satisfaction. [ 24 31 32 ] In our study, we demonstrated that the burnout levels of the participants who have low income have high burnout level.…”
Section: Discussionmentioning
confidence: 70%
“…The current literature lacks the studies that investigate the relationship of low financial income and work satisfaction. [ 24 31 32 ] In our study, we demonstrated that the burnout levels of the participants who have low income have high burnout level.…”
Section: Discussionmentioning
confidence: 70%
“…Organization citizenship behaviour is defined as 'individual behaviour that is discretionary, not directly or explicitly recognized by the formal reward system and in the aggregate promotes the efficient and effective functioning of the organization' (Organ 1988, p. 4). Nurses' engagement and citizenship behaviours have been recognized as critical skills for enhancing quality of patient care and well-being (Abdelhadi & Drach-Zahavy 2012, Hyde et al 2013, Bailey et al 2015, Bolino et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…In parallel with the rising levels of interest in engagement within the practitioner community, the years since William Kahn (1990) published his seminal academic study on engagement have witnessed a significant growth in engagement research amongst scholars. A recent structured search of academic databases found that 5,771 items had been published during this time (Bailey et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%